2021
DOI: 10.3389/fneur.2021.731606
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Tai Chi and Stretching Exercises Based on a Smartphone Application for Patients With Parkinson's Disease: A Protocol for a Randomized Controlled Trial

Abstract: Introduction: Parkinson's disease (PD) is a common neurodegenerative disease that seriously impairs patients' quality of life, and increases the burden of patients and caregivers. Both drugs and exercise can alleviate its motor and non-motor symptoms, improving the quality of life for PD patients. Telehealth, an increasingly popular tool, makes rehabilitation accessible at home, overcoming the inconvenience of traffic and scheduling. Care-PD is a phone application designed for rehabilitation training, which pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Prior to the pandemic, research has shown that virtual-based CITs are potentially beneficial to patients with neurological conditions who want to improve self-care and track their symptoms. 8 , 20 Studies demonstrated that the use of virtual CITs put increased responsibility on the patient, which enabled them to feel more involved in their care and motivate them to maintain a healthy lifestyle. 8 , 20 During the pandemic, and with the associated increased use of telehealth services, 4 we found several key observations regarding CIT use: (1) patients who reported postponing medical treatment were more likely to seek CITs; (2) younger patients were more likely to employ mobile/virtual CITs; (3) virtual exercise, virtual psychotherapy, and relaxation/meditation smartphone applications were the most reported types of virtual CITs employed; (4) patients who reported postponing medical treatment were more likely to seek complementary and integrative therapies (CITs).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the pandemic, research has shown that virtual-based CITs are potentially beneficial to patients with neurological conditions who want to improve self-care and track their symptoms. 8 , 20 Studies demonstrated that the use of virtual CITs put increased responsibility on the patient, which enabled them to feel more involved in their care and motivate them to maintain a healthy lifestyle. 8 , 20 During the pandemic, and with the associated increased use of telehealth services, 4 we found several key observations regarding CIT use: (1) patients who reported postponing medical treatment were more likely to seek CITs; (2) younger patients were more likely to employ mobile/virtual CITs; (3) virtual exercise, virtual psychotherapy, and relaxation/meditation smartphone applications were the most reported types of virtual CITs employed; (4) patients who reported postponing medical treatment were more likely to seek complementary and integrative therapies (CITs).…”
Section: Discussionmentioning
confidence: 99%
“…8,20 Studies demonstrated that the use of virtual CITs put increased responsibility on the patient, which enabled them to feel more involved in their care and motivate them to maintain a healthy lifestyle. 8,20 During the pandemic, and with the associated increased use of telehealth services, 4 we found several key observations regarding CIT use: (1) patients who reported postponing medical treatment were more likely to seek CITs; (2) younger patients were more likely to employ mobile/virtual CITs;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation